Financial Constraints, Debt Capacity, and the Cross‐section of Stock Returns - HAHN, JAEHOON; LEE, HANGYONG (Journal of Finance, 2009)
ABSTRACT Building on a model of corporate investment under collateral constraints, we develop and test a hypothesis on the differential effect of debt capacity on stock returns across financially constrained and unconstrained firms. Consistent with the hypothesis, we find that debt capacity is a significant determinant of stock returns only in the cross‐section of financially constrained firms, after controlling for beta, size, book‐to‐market, leverage, and momentum. The findings suggest that cross‐sectional differences in corporate investment behavior arising from financial constraints, predicted by theories of imperfect capital markets and supported by empirical evidence, are reflected in the stock returns of manufacturing firms.